Investigation Of Factors Influencing The Determination Of Discount Rate In The Economic Evaluation Of Mineral Development Projects ? Synopsis - S-J. Park (The Southern African Institute of Mining and Metallurgy, 2011)
When evaluating mining investment opportunities, one should consider the risks associated with mineral exploration and development. These are commonly classified as technical, economic, and political risks, and are accounted for in the investment decision by changing the discount rate. Thus, a company may use different discount rates associated with varying risks in order to compensate for the variability of success. The discount rate has a tremendous effect on the economic evaluation of mineral projects. Even when all other factors used as inputs for calculating the NPV (net present value) are equal, the project under consideration may be accepted or rejected depending upon the discount rate. Determining a realistic discount rate for a given project is therefore the most difficult and important aspect of cash flow analysis. It should be determined with the consideration of proper technical, economic, and political conditions surrounding the specific project undergoing economic evaluation. One key problem for determining the appropriate discount rate is that it typically depends more on subjective perception of the degree of risk or other experience factors than on a systematic approach. Thus, this study aims to identify, analyse, and document the type, role, and impact of risk factors influencing the determination of discount rates, and then to determine discount rate by using the aforementioned factors.